On the uniform convergence of the Fourier series on a closed domain - Rakhimov, Abdumalik A. (Steklov Mathematical Institute RAS, 2017)
The uniform convergence on a closed domain is studied of eigenfunction expansions of continuous functions belonging to function spaces with mixed norm.